Differentiation of jurisdiction and the constitutional right of the defendant to trial by jury - Akhpanov А.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
The article examines the theoretical, legislative, institutional, technical, and legal aspects of the administration of criminal justice related to ensuring and observing the constitutional right of a defendant to a trial by jury. Within the framework of the doctrinal interpretation of the relevant norms on this form of criminal proceedings, the article focuses on the conditionality and alternativeness of this right of the defendant. The article investigates criteria for referring criminal cases to the jurisdiction of a court with the participation of a jury. The author considers a legal assessment of legal conflicts and a gap in legal regulation arising in judicial practice in differentiating the jurisdiction of criminal cases to a court with the participation of a jury. There was considered the issue of the retroactive effect of the provisions of the law on referring to the consideration by a court with the participation of a jury of the category and composition of criminal offenses, which come into force on January 1, 2023. The author studied foreign legislation and the practice of differentiating the jurisdiction of the jury.